Multilobated nuclei in Waldenström’ macroglobulinaemia - Metzgeroth, Georgia; Sick, Christian; Maywald, O.; Schatz, M.; Kuhn, Ch.; Hehlmann, Rüdiger; Hastka, Jan (European journal of haematology, 2003)
Abstract: We report a case of Waldenström’ macroglobulinaemia, where the bone marrow analysis showed an almost complete infiltration by a heterogeneous population, consisting of 80% small lymphoplasmacytoid cells and 20% large atypical cells with multilobulated nuclei. Both cell populations were CD19+ and CD38+ and contained IgM. Fluorescence in situ hybridization analysis with a chromosome 8 painting probe on interphase nuclei revealed only two signals in each cell, including in those with multiple nuclei. Our findings suggest that the multilobulated nuclear structures are diploid and originate from a single nucleus. In contrast to the published multiple myeloma cases, our patient showed good response to chemotherapy. After successful chemotherapy, the morphology of the lymphoma changed into typical lymphoplasmacytoid lymphoma. The multilobulated population was no longer detectable. Five years after the initial diagnosis, the patient is still alive and in good health.